Etiology and Outcome of Isolated Fetal Ascites: A Systematic Review. Issue 6 (December 2021) - Horgan, Rebecca; Youssef, Julia A.; Levy, Ariel T.; Berger, Seth I.; Dreux, Sophie; Brizot, Maria L.; Boutall, Alison; Abuhamad, Alfred Z.; Angarita, Ana M.; Al-Kouatly, Huda B.
Abstract : OBJECTIVE: To describe the etiology of isolated fetal ascites and associated perinatal outcomes, and to assess the progression of isolated fetal ascites to fetal hydrops. DATA SOURCES: PubMed, Cochrane Library, Scopus, and ClinicalTrials.gov databases were searched using the following keywords: "fetus" OR "foetal" OR "fetal" OR "foetus" AND "ascites" from inception to February 2020. The search was limited to the English language. METHODS OF STUDY SELECTION: A total of 1, 983 articles were identified through the search strategy. All studies containing five or more cases of isolated fetal ascites were included. TABULATION, INTEGRATION, AND RESULTS: Eleven studies, involving 315 cases of isolated fetal ascites, were eligible for inclusion in this systematic review. All included studies were evaluated using the tool for evaluating the methodologic quality of case reports and case series described by Murad et al. Data were summarized using narrative review and descriptive statistics. Two-tailed Fisher exact P values calculated from hypergeometric distribution were used to compare outcome by etiology. CIs were calculated with Clopper-Pearson exact binomial interval. The etiologies of isolated fetal ascites are genitourinary (24%), gastrointestinal (20%), viral or bacterial infections (9%), cardiac (9%), genetic disorders not otherwise categorized (8%), chylous ascites (6%), metabolic storage disorders (3%), other structural disorders (4%), other causes (4%) and idiopathic (13%). Survival is most favorable for cases of isolated fetal ascites as a result of chylous (100%), idiopathic (90%), gastrointestinal (77%) and genitourinary (77%) etiologies. Survival is least favorable for fetuses with isolated fetal ascites as a result of structural disorders (25%), cardiac etiology (32%) and metabolic storage disorders (33.3%). When pregnancy terminations were excluded, survival rates were similar between fetuses diagnosed at or after 24 weeks of gestation compared with those diagnosed at less than 24 weeks (74% vs 61%, P =.06). Progression of fetal ascites to fetal hydrops occurred in 6.6% (95% CI 3.6–9.6%) (17/259) of cases when pregnancies that were terminated were excluded. CONCLUSION: Isolated fetal ascites has a diverse etiology. Outcome is related to the etiology of isolated fetal ascites. In the majority of cases, fetal ascites does not progress to fetal hydrops. SYSTEMATIC REVIEW REGISTRATION: PROSPERO, CRD42020213930. Abstract : Isolated fetal ascites has a wide differential diagnosis and rarely progresses to fetal hydrops.